What Eye Movements Reveal About Deaf Readers. (June 2015) - Bélanger, Nathalie N.; Rayner, Keith
Levels of illiteracy in deaf populations around the world have been extremely high for decades and much higher than the illiteracy levels found in the general population. Research has mostly focused on deaf readers' difficulties rather than on their strengths, but having a better grasp of deaf readers' strengths could inform reading education. Deaf readers are a unique population. They process language and the world surrounding them mostly via the visual channel, and this greatly affects how they read or might learn to read. The study of eye movements in reading provides highly sophisticated information about how words and sentences are processed, and our research with deaf readers reveals the importance of their uniqueness.